Immunoproteomic Analysis of Potentially Severe Non‐Graft‐Versus‐Host Disease Hepatitis After Allogenic Bone Marrow Transplantation1. Issue 2 (8th January 2013) - Beleoken, Elvire; Sobesky, Rodolphe; Le Caer, Jean‐Pierre; Le Naour, François; Sebagh, Mylène; Moniaux, Nicolas; Roche, Bruno; Mustafa, Mohammad Zahid; Guettier, Catherine; Johanet, Catherine; Samuel, Didier; Bouhris, Jean‐Henri; et al.
Abstract The development of potentially severe non‐graft‐versus‐host disease (GVHD) hepatitis resembling autoimmune hepatitis (AIH) has been reported after bone marrow transplantation (BMT). The aim of this study was to better characterize this form of hepatitis, particularly through the identification of autoantigens recognized by patient sera. Five patients who received an allogeneic BMT for the treatment of hematological diseases developed liver dysfunction with histological features suggestive of AIH. Before and during the onset of hepatic dysfunction, sera were tested on immunoblottings performed with cytosolic, microsomal, mitochondrial, and nuclear proteins from rat liver homogenate and resolved by two‐dimensional electrophoresis. Antigenic targets were identified by mass spectrometry. During the year that followed BMT, all patients presented with GVHD. Acute hepatitis then occurred after the withdrawal, or during the tapering, of immunosuppressive therapy. At that time, no patients had a history of liver toxic drug absorption, patent viral infection, or any histopathological findings consistent with GVHD. Immunoreactive spots stained by sera collected at the time of hepatic dysfunction were more numerous and more intensely expressed than those stained by sera collected before. Considerable patient‐dependent pattern heterogeneity was observed. Among the 259 spots stained exclusively by sera collected at the time of hepatitis, a total of 240 spots were identified, corresponding to 103 different proteins. Twelve of them were recognized by sera from 3 patients. Conclusions: This is the first immunological description of potentially severe non‐GVHD hepatitis occurring after BMT, determined using a proteomic approach and enabling a discussion of the mechanisms that transform an alloimmune reaction into an autoimmune response. Any decision to withdraw immunosuppression after allogeneic BMT should be made with caution. (HEPATOLOGY 2013)